2022
DOI: 10.1039/d2ay00372d
|View full text |Cite
|
Sign up to set email alerts
|

Cationic AIEgen micelle-improved chemiluminescent H2O2 assay by integrating reactant approach and CRET

Abstract: The enhancement of chemiluminescence (CL) intensity is significant to exploit chemiluminescent detection systems with improved sensitivity. In this study, cationic surfactant with intrinsic aggregation-induced emission emitter (AIEgen) has been applied...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 30 publications
(35 reference statements)
0
4
0
Order By: Relevance
“…Based on the respective merits of Fe 3 O 4 @SiO 2 and MSNs, for example, high magnetic separation efficiency of Fe 3 O 4 @SiO 2 microspheres and high enzymes loading capacity of MSNs, Fe 3 O 4 @SiO 2 -Ab2 and MSN-HRP/Ab1 were rationally designed and synthesized as capture probes and detection probes for The core-satellite sandwich CL immunoassay concept is based on the widely accepted mechanism that HRP can efficiently catalyze the oxidization of luminol and generate intense CL signal in the presence of hydrogen peroxide. [34,35] The pH of solution and the concentration of luminol have great influence on the CL signal intensity. Particularly, p-bromophenol acted as a CL enhancer can significantly accelerate the cyclic transformation of HRP and the electron transfer between luminol molecules and radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Based on the respective merits of Fe 3 O 4 @SiO 2 and MSNs, for example, high magnetic separation efficiency of Fe 3 O 4 @SiO 2 microspheres and high enzymes loading capacity of MSNs, Fe 3 O 4 @SiO 2 -Ab2 and MSN-HRP/Ab1 were rationally designed and synthesized as capture probes and detection probes for The core-satellite sandwich CL immunoassay concept is based on the widely accepted mechanism that HRP can efficiently catalyze the oxidization of luminol and generate intense CL signal in the presence of hydrogen peroxide. [34,35] The pH of solution and the concentration of luminol have great influence on the CL signal intensity. Particularly, p-bromophenol acted as a CL enhancer can significantly accelerate the cyclic transformation of HRP and the electron transfer between luminol molecules and radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The core‐satellite sandwich CL immunoassay concept is based on the widely accepted mechanism that HRP can efficiently catalyze the oxidization of luminol and generate intense CL signal in the presence of hydrogen peroxide. [ 34,35 ] The pH of solution and the concentration of luminol have great influence on the CL signal intensity. Particularly, p ‐bromophenol acted as a CL enhancer can significantly accelerate the cyclic transformation of HRP and the electron transfer between luminol molecules and radicals.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that cationic micelle can adsorb anionic reactants and benefit the CL reaction. [ 39,40 ] At pH 7.4, the C 8 ‐TPE‐C 4 TAB micelle was positively charged (+11.0 mV) because of the outside ternary ammonium cation (Figure S6), while luminol was negatively charged (−4.8 mV). The electrostatic attraction between positively charged C 8 ‐TPE‐C 4 TAB micelle and negatively charged luminol dianion/peroxide anion easily leads to surface adsorption and enrichment of reactants.…”
Section: Resultsmentioning
confidence: 99%
“…It is reported that cationic micelle can adsorb anionic reactants and benefit the CL reaction. 39 At pH 7.4, the C 8 -TPE-C 4 TAB micelle was positively charged (+11.0 mV) because of the outside ternary ammonium cation (Figure S5), while luminol was negatively charged (-4.8 mV). The electrostatic attraction between positively charged C 8 -TPE-C 4 TAB micelle and negatively charged luminol dianion/peroxide anion easily leads to surface adsorption and enrichment of reactants.…”
Section: Resultsmentioning
confidence: 99%